Local application of a proteasome inhibitor enhances fracture healing in rats. Issue 8 (25th May 2015) - Yoshii, Toshitaka; Nyman, Jeffry S.; Yuasa, Masato; Esparza, Javier M.; Okawa, Atsushi; Gutierrez, Gloria E.
ABSTRACT The ubiquitin/proteasome system plays an important role in regulating the activity of osteoblast precursor cells. Proteasome inhibitors (PSIs) have been shown to stimulate the differentiation of osteoblast precursor cells and to promote bone formation. This raises the possibility that PSIs might be useful for enhancing fracture healing. In this study, we examined the effect of the local administration of PSI on fracture repair in rats. The effects of treatment on the healing of a fractured femur were assessed based on radiographs, micro‐computed tomography (μCT) analysis, biomechanical testing, and histological analysis. PSI enhanced osteogenic differentiation in bone marrow‐ and periosteum‐derived mesenchymal progenitor cells in vitro. Moreover, the local administration of PSI in vivo promoted fracture healing in rats, as demonstrated by an increased fracture callus volume in radiographs at 2 weeks post‐fracture, and improved radiographic scores. By week 4, PSI treatment had enhanced biomechanical strength and mineral density in the callus as assessed using bending tests, and μCT, respectively. Histological sections demonstrated that PSI treatment accelerated endochondral ossification during the early stages of fracture repair. Although further investigations are necessary to assess its clinical use, the local administration of PSIs might be a novel, and effective therapeutic approach for fracture repair. © 2015 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 33:1197–1204, 2015.